Validity and predictability of mid-upper arm circumference for nutrition screening in outpatient preschoolers with cerebral palsy - Zhou, Hongyu; Peng, Tingting; Wei, Mou; Zhang, Jingbo; Zhao, Yiting; Le, Wen; Fan, Danxia; Qiu, Shaihong; Zheng, Yuai; Lin, Qiujin; Zheng, Yun; Ma, Liying; et al. (Frontiers in Nutrition, 2025)
AimEvaluating the nutritional status of children with cerebral palsy (CP) is difficult due to spasticity and contractures. Mid-upper arm circumference (MUAC) is a potential screening tool for malnutrition in children with CP, but its effectiveness is unproven. This study aims to provide evidence on the psychometric qualities of MUAC for clinical use and establish optimal cutoffs for preschoolers with CP.MethodsChildren with CP aged 12–60 months (n = 937) were recruited from 24 hospitals across 13 provinces in China for the cross-sectional study, while those had genetic or metabolic diseases were excluded. Weight, length/height and MUAC were obtained from participants. Weight and length/height were calculated into Z scores by using WHO Anthro software to assess the nutritional status. The sensitivity and specificity of the WHO-recommended MUAC cutoffs were calculated. The Spearman’s rank correlation, Receiver operating characteristic (ROC) curve, and Youden Index were conducted to establish the optimal MUAC cutoffs for preschoolers with CP.ResultsCompared to Z score cutoffs, WHO-recommended MUAC cutoffs showed high specificity but low sensitivity for malnutrition. MUAC significantly correlated with weight-for-length/height Z score (r = 0.606), weight-for-age Z score (r = 0.557), length/height-for-age Z score (r = 0.276), and BMI-for-age Z score (r = 0.575). The optimal MUAC cutoffs for mild, moderate, and severe undernutrition were 15.35, 15.05, and 14.35 cm, respectively; the optimal cutoffs for overweight and obesity were 17.55 and 20.4 cm, respectively.ConclusionOur study suggests that MUAC is a useful tool for screening the nutritional status of children with CP. However, the WHO-recommended MUAC cut-off may not be suitable for preschool with CP. We estimated that the optimal MUAC cutoffs were 15.35 cm for mild undernutrition, 15.05 cm for moderate undernutrition, and 14.35 cm for severe undernutrition, and 17.55 cm for overweight and 20.4 cm for obesity in preschool with CP.Clinical trial registrationwww.chictr.org.cn, ChiCTR2000033869.